The Effect of Easy Perceptions and Risk Perceptions on Interest in Using Electronic Money Paying Systems in Ecommerce Shopee Applications - Bella Melati Sukma; Renny Dwijayanti (Jurnal Mantik, 2022)
The research use questionnaire distribution. This study aims to determine the effect of perceived convenience and perceived risk on interest in using electronic money payment systems in the Shopee E-Commerce application. The independent variables studied were perceived ease and risk. Usage variable is usage interest. The following types of research are quantitative research. The population in the study are active students of the Faculty of Economics and Business, State University of Surabaya, class 2018 – 2021 who use the ShopeePay payment system, and get a sample by opening 100 respondents. Using a non-probability sampling technique with a purposive sampling approach. Based on the analysis of this study, it was found that the variable perception of ease had a positive and significant effect on interest in use, and the variable perception had a positive value and had no effect on interest in use. Meanwhile, the perception of convenience (X?) and the perception of risk (X?) together have a positive effect on interest in using (Y) in the Shopee E-Commerce application.